HUBUNGAN DERAJAT KLINIS DENGAN KADAR FERITIN PENYANDANG THALASSEMIA β DI RSUD ARIFIN ACHMAD - Adriyan Satria; Elmi Ridar; Lucyana Tampubolon (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
AbstractThalassemia is a genetic disorder which there is interference with the synthesis of hemoglobin that causes a decreased of synthesis of α or β chain, If the abnormalities are β chain called β thalassemia. People with thalassemia need transfusion of red blood in rest of their life to maintain sufficient hemoglobin level, but the result in increased level of iron overload in body which can cause complication. This study aims to see the description and the correlation between clinical severity with ferritin level of β thalassemia at Arifin Achmad Hospital in Riau province. The method used is analytic with cross sectional approach. Disease severity assessed by Thailand score whereas ferritin level through laboratory test. Of 59 people with thalassemia there are as many as 49 people (83.1%) with moderate disease severity and 10 people (16.9%) with severe disease severity, whereas ferritin levels <1000 ng/ml as many as 6 people (10.2%), 1000-2500 ng/ml as many as 14 people (23.7%) and >2500 ng/ml as many as 39 people (66.1%). After analysis, there is no correlation between disease severity with ferritin level (p>0.05). The conclusion of this study, the highest data are thalassemia with moderate disease severity and ferritin level >2500 ng/ml, also there is no correlation between disease severity with ferritin level.Keyword: β thalassemia, disease severity, ferritin level